The aerodynamics of micro air vehicles: technical challenges and scientific issues. (1st January 2014) - Moschetta, Jean-Marc
Micro air vehicles raise numerous design problems associated to the size reduction: lower aerodynamic and propulsion efficiencies, higher sensitivity to atmospheric turbulence, low-density energy of electric propulsion, etc. The paper discusses some of the most important design issues and analyses the aerodynamic challenges encountered in the field of MAVs. A number of novel aerodynamic configurations combining rotors and fixed-wing are proposed and discussed in order to recover efficiency and maneuverability at low speeds.